Pembelajaran Berbasis Proyek Berbentuk Terarium Dalam Botani Tingkat Rendah: Persepsi Mahasiswa Pendidikan Biologi: Project-Based Learning in the Form of a Terrarium in Lower Botany: Perceptions of Biology Education Students - Makkadafi, Suparno Putera; Turista, Dora Dayu Rahma (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2025)
Lower-level botany learning has been carried out using conventional lecture methods. Learning becomes less meaningful for students because students tend to be passive. The purpose of this study was to see how students perceive the application of the project-based learning (PjBL) model in lower-level botany courses. This research was conducted using a quantitative research model with a survey method. Data collection was carried out by giving questionnaires to students. As many as 85.7% of students stated that they felt that their understanding of lower-level botany had improved and 80% expressed interest in lower-level botany learning with PjBl. As many as 82.9% stated that they were able to design a terrarium well and 85.7% were able to state that PjBl helped them identify the morphology of cryptogamae. As many as 74.3% of students stated that they were motivated by group cooperation and 71.4% of them were able to link theory and practice. The final result was that 88.6% of students felt that this learning method improved their understanding of cryptogamae. Overall, low-level botany learning with PjBL for biology education students at Mulawarman University can improve students' understanding and interest in low-level botany courses. Key words: Project-Based Learning (PjBL), Lower-Level Botany, Terrarium, Student Perception